Pengaruh Kepercayaan, Promosi Gratis Ongkir, Online Customer Review Dan Cash On Delivery Terhadap Keputusan Pembelian Pada Marketplace Tiktok Shop (Studi Kasus Pada Mahasiswa di Kota Malang) - Putri Wulan Sari; Rois Arifin; Muhamad Tody Arsyianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to test and explain the influence of trust, free shipping promotions, online customer reviews and cash on delivery on purchasing decisions on the TikTok Shop Marketplace case study on students in Malang City. This study uses a quantitative approach which uses the Malhotra formula in order to determine the sample because the population is still not known for sure, seeing from the calculation results of the Malhotra formula to get the result of the number of samples as many as 90. To solve the problems in this study using the help of SPSS version 25 in analyzing validity tests, reliability tests, normality tests, classical assumption tests, hypothesis tests, multiple linear regression tests and adjusted determination coefficient tests R2. The results of this study, namely trust, free shipping promotions, online customer reviews and cash on delivery simultaneously have a positive and significant effect on purchasing decisions and trust has a positive insignificant effect on purchasing decisions and free shipping promotions, online customer reviews and cash on delivery have a significant positive effect on purchasing decisions. Keywords: Trust, Free Shipping Promotion, Online Customer Reviews, Cash On Delivery, Purchasing Decision